Rubric-based tools to support the monitoring and assessment of Bachelor's Final Projects - Verónica MORENO OLIVER; Davinia HERNÁNDEZ-LEO (Ediciones Universidad de Salamanca, 2015)
The role of Bachelor's Final Projects (BFP) in Engineering Education is critical since it offers the opportunity for students to integrate and employ specific and transversal competences they have developed along the degree. However, given the special characteristics of this curriculum component (personalized according to the student's interests, the number of teachers involved, the changing assessment boards, etc.), the systematization of its formative and summative assessment has been extensively recognized as problematic but highly necessary. To face this problem, there are several recent initiatives reported in the literature that propose a set of rubrics as tools for project advisors and board members to structure the assessment. In this paper, we report the experience in the Engineering School at Universitat Pompeu Fabra (Barcelona) employing a rubricbased approach as part of an assessment guide (with a web-based support tool) for BFP. The guide has been evaluated using quantitative and qualitative data gathering techniques used before, during and after the rubrics use, and the results provide insights about its utility, pertinence, user-friendliness, preciseness and actual adoption. Findings led to the provision an additional feature in the web-based tool for the integrated assessment of transversal and specific competences and a view of a summarized version of the rubrics that can be used using mobile devices.